Analisis Biaya Perjalanan Lalu Lintas Akibat Adanya Pengaruh Hambatan Samping pada Ruas Jalan Raya Canggu - I Gede Adi Pramesta; I Gusti Ngurah Nyoman Wismantara; Dewa Ayu Putu Adhiya Garini Putri (Universitas Pendidikan Nasional, 2022)
Canggu Village is a village located in the tourist area of southern Bali. resulting in economic activity originating from tourism activities. transportation has greatly increased. especially in traffic conditions. this is the interest of researchers to analyze the cost of traffic travel due to side barriers. This method is to ensure the presentation of road fractions referring to the 1997 MKJI and the calculation of the BOK for vehicles involving the strategy of the Ministry of Public Works in 2005. Meanwhile, the calculation of the BOK for bicycles refers to the DLLAJ strategy. for the Province of Bali - PTS Consultant 1999. The consequences of this study are: 1) The current appearance of the Canggu Highway with the presence of side barriers are: The capacity of the street portion is 2.883 pcu/hour at top hours in the first part of the day. evening. what's more, evening. The degree of saturation or v/c ratio on the existing road is 0.513 for the morning peak hours. 0.469 and 0.496 for the afternoon and evening peak hours. The speed of light vehicles during the morning top hours is 13.48 km/hour. the afternoon peak hours are 14.11 km/hour and the afternoon peak hours are 13.48 km/hour hours. The level of service for each peak hour is at service level F. 2) The total traffic cost due to the presence of side barriers per 12 hours of observation is Rp. 4.372.938.06. and the cost of travel in each peak hour is for the morning peak hour at 07.15-08.15 Rp. 356.444.50. the peak hour at 12.15-13.15 is Rp. 297.484.08 peak hours in the afternoon at 16.15-17.15 for Rp. 707.875.89.